Growth inhibition of Hydrilla verticillata by freshwater fungi - Triadiati Triadiati; Nampiah Sukarno; IRMA SITI RAHMAH (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Triadiati T, Sukarno N, Rahmah IS. 2021. Growth inhibition of Hydrilla verticillata by freshwater fungi. Biodiversitas 22: 2876-2882. The uncontrolled growth of hydrilla (Hydrilla verticillata (L.f.) Royle) in Mekarsari Fruit Garden, Bogor causes various losses. A Freshwater fungus is one of the alternatives to control hydrilla growth. Therefore, the study aimed to investigate the damage and growth inhibition of hydrilla using freshwater fungi. Freshwater fungi were isolated from Lake Mekarsari Fruit Garden. Hydrilla growth characteristics observed were stem length, stem nodus number, number of healthy leaves, leaf number, leaf damage, wet and dry weight. The results showed that a total of seven isolates of freshwater fungi were obtained from Lake Mekarsari Fruit Garden. Two species, i.e. Myrothecium sp. and Stachybotrys sp. were selected to control hydrilla growth. Fungal treatment reduced the stem length and leaf number of hydrilla. The combination of both fungal isolates showed less leaf damage than Myrothecium sp. The damage of hydrilla leaves by Myrothecium sp. and Stachybotrys sp. were 98.07% and 78.71%, respectively.